GOOD CORPORATE GOVERNANCE DAN PERMODALAN PERBANKAN: PERAN MANAJEMEN RISIKO DI ERA PRA-COVID - Nurianah; Beni Sucipto; Irea Arahima (STIE PGRI Dewantara Jombang, 2025)
This study investigates the effect of Good Corporate Governance (GCG) on bank capital, with risk management serving as an intervening variable. The research focuses on Indonesian banks during the period 2015–2019, representing the pre-Covid era when economic conditions were relatively stable and had not yet experienced major shocks from the pandemic. GCG is considered a mechanism that strengthens public trust and enhances the quality of bank management, while risk management functions as a mediating process that translates sound governance into effective risk mitigation strategies. A quantitative approach was employed, using the Capital Adequacy Ratio (CAR) to measure capital adequacy and Non-Performing Loans (NPL) to assess risk management. The sample comprised all banks listed on the Indonesia Stock Exchange (IDX) during 2015–2019, resulting in 1,150 annual reports from 46 banks. Hypothesis testing was conducted using path analysis. The findings indicate that GCG has a direct effect on NPL, while NPL does not exert a direct effect on CAR. In contrast, without the intervening variable, GCG demonstrates an indirect effect on CAR. The results provide insights into the extent to which GCG contributes to strengthening bank capital through risk management and offer practical implications for regulators and banking practitioners in maintaining financial sector stability.